Ticagrelor Associated Heart Block: The Need for Close and Continued Monitoring - Munish Sharma; Daniel A. N. Mascarenhas (Case Reports in Cardiology)
Ticagrelor is an antiplatelet agent prescribed to prevent the development of adverse cardiac events after acute coronary syndrome (ACS). According to the PLATO trial, ticagrelor is associated with ventricular pauses in the first week of treatment; however, these episodes were felt to be asymptomatic and nonfatal to the patient. We present a case of ticagrelor related second-degree type II heart block causing severe dizziness and diaphoresis that resolved after discontinuation of the medication.